Acute retinal detachment induced by the Valsalva manoeuvre in morning glory disc anomaly - Fajgenbaum, Mark A P (BMJ Case Rep, 2018)
We present a case in which a large, bullous, predominantly inferior, serous retinal detachment developed acutely after the Valsalva manoeuvre (from a coughing fit) in an eye with morning glory disc anomaly. We postulate that a rapid alteration in intracranial pressure was transmitted through the cavitary disc defect. This allowed a sudden influx of cerebrospinal fluid and/or liquefied vitreous into the subretinal space. This previously unreported case provides important evidence for the role of intracranial pressure fluctuations in the pathogenesis of macular schisis and neurosensory detachment secondary to optic disc cavitations.